Proyecto educativo para fortalecer la práctica de los derechos de los niños en la sección inicial de la Unidad Educativa "Liceo del Valle" - Orbe Beltrán, Edith Azucena (2015)
At the present the rights of children has always been a very important part of social, educational, family and the state, we all have an obligation to assist and protect children to ensure their full and harmonious development and to stimulate their areas: cognitive, psychomotor, and affective language partner. UNICEF and others have tried to promote their cognition of the rights of children, in order to both individuals and institutions that promoter spect and can make everyone apply them. The rights that are related to education are: nonviolence, love and understanding, the right to play, free expression, information, freedom of thoughts, family, education for disabled children, the diversity of culture and health. On the right to education should be required consistency and quality, where their dignity is respected and increase their ability to live a decent life, teachers have the primary responsibility in teaching children having rights and duties, in addition to formattitudes of respect for themselves and for others. For this reason, it is essential that teacher sup date their know ledge on the subject through an educational project that encourages teachers and student stotraininan environment of absoluter espect takingin to account especially the rights of children. This project is base don the fulfillment of the rights of childrenof4-5years of Liceo del Valle Education Unit, which consists of supporting files, surveys, videos and training to teachers, each of these elements are part a consistent and effective in getting prevails above all the rights of children.